Accreditation of Libraries and Documentation in Costa Rica Escuela de Bibliotecología, Documentación e Información, National University - Ugalde Víquez, Aracelly (2008)
This research aims to provide an idea of the dimension and formal structure of the career, from an intrinsic and extrinsic perspective that facilitates the identification of obstacles, the planning and proposal of improvement alternatives based on scientific results. This report presents the methodology used in the self-evaluation and accreditation processes to know the perspective of the informants about the academic activities, the results of the analysis of the systematization of the collected information, the experience obtained throughout the four years accredited in the School of Library, Documentation and Information and the lessons learned in the process; considering as base the guidelines of the accrediting entity, the National System of Accreditation of Higher Education (SINAES). This exercise can be used as a manual of practices to guarantee quality educational processes, as a methodology to follow up the activities that must be carried out in the processes of accreditation of university careers and as an input to define aspects of curriculum evaluation.